Activation of Ni Particles into Single Ni–N Atoms for Efficient Electrochemical Reduction of CO2. Issue 5 (5th December 2019) - Fan, Qun; Hou, Pengfei; Choi, Changhyeok; Wu, Tai‐Sing; Hong, Song; Li, Fang; Soo, Yun‐Liang; Kang, Peng; Jung, Yousung; Sun, Zhenyu
Abstract: Electrochemical reduction of carbon dioxide (CO2 ) to fuels and value‐added industrial chemicals is a promising strategy for keeping a healthy balance between energy supply and net carbon emissions. Here, the facile transformation of residual Ni particle catalysts in carbon nanotubes into thermally stable single Ni atoms with a possible NiN3 moiety is reported, surrounded with a porous N‐doped carbon sheath through a one‐step nanoconfined pyrolysis strategy. These structural changes are confirmed by X‐ray absorption fine structure analysis and density functional theory (DFT) calculations. The dispersed Ni single atoms facilitate highly efficient electrocatalytic CO2 reduction at low overpotentials to yield CO, providing a CO faradaic efficiency exceeding 90%, turnover frequency approaching 12 000 h −1, and metal mass activity reaching about 10 600 mA mg −1, outperforming current state‐of‐the‐art single atom catalysts for CO2 reduction to CO. DFT calculations suggest that the Ni@N3 (pyrrolic) site favors *COOH formation with lower free energy than Ni@N4, in addition to exothermic CO desorption, hence enhancing electrocatalytic CO2 conversion. This finding provides a simple, scalable, and promising route for the preparation of low‐cost, abundant, and highly active single atom catalysts, benefiting future practical CO2 electrolysis. Abstract : The facile transformation of Ni particles in carbon nanotubes into single Ni atoms with a NiN3 moiety is reported, surrounded with porous N‐doped carbon sheaths by in situ thermal diffusion. The dispersed Ni single atoms facilitate electrocatalytic CO2 reduction at low overpotentials, delivering excellent selectivity, stability, and high turnover frequency.